2021
DOI: 10.3390/cells10040822
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Signaling by TRPV4 Channels in Respiratory Function and Disease

Abstract: Members of the transient receptor potential (TRP) superfamily are broadly expressed in our body and contribute to multiple cellular functions. Most interestingly, the fourth member of the vanilloid family of TRP channels (TRPV4) serves different partially antagonistic functions in the respiratory system. This review highlights the role of TRPV4 channels in lung fibroblasts, the lung endothelium, as well as the alveolar and bronchial epithelium, during physiological and pathophysiological mechanisms. Data avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 117 publications
(142 reference statements)
0
11
0
Order By: Relevance
“…TRPV4 cation channels elicit focal Ca 2+ influx events at the plasma membrane (Ca 2+ sparklets), allowing for localized signal targeting and providing a trigger for larger Ca 2+ -induced Ca 2+ release events (i.e., from the endoplasmic reticulum) ( Sullivan et al, 2012 ; Lin et al, 2015 ; Heathcote et al, 2019 ; McFarland et al, 2020 ). Growing evidence supports involvement of these channels in shear stress and agonist-mediated endothelial signaling, and changes in TRPV4 signaling are linked to disease states including hypertension, diabetes and pulmonary edema ( Hartmannsgruber et al, 2007 ; Mendoza et al, 2010 ; Sonkusare et al, 2012 ; Ma et al, 2013 ; Monaghan et al, 2015 ; Zhang et al, 2018 ; Daneva et al, 2021 ; Rajan et al, 2021 ). In the current study, we observed TRPV4 channels expressed in the intima as well as the media of peripheral arteries, and even within neointima of arteries from CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4 cation channels elicit focal Ca 2+ influx events at the plasma membrane (Ca 2+ sparklets), allowing for localized signal targeting and providing a trigger for larger Ca 2+ -induced Ca 2+ release events (i.e., from the endoplasmic reticulum) ( Sullivan et al, 2012 ; Lin et al, 2015 ; Heathcote et al, 2019 ; McFarland et al, 2020 ). Growing evidence supports involvement of these channels in shear stress and agonist-mediated endothelial signaling, and changes in TRPV4 signaling are linked to disease states including hypertension, diabetes and pulmonary edema ( Hartmannsgruber et al, 2007 ; Mendoza et al, 2010 ; Sonkusare et al, 2012 ; Ma et al, 2013 ; Monaghan et al, 2015 ; Zhang et al, 2018 ; Daneva et al, 2021 ; Rajan et al, 2021 ). In the current study, we observed TRPV4 channels expressed in the intima as well as the media of peripheral arteries, and even within neointima of arteries from CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to show the expression of TRPV4 in both AT1 and AT2 cells and identified emphysema-like changes in the lungs of older TRPV4−/− mice, which favor ischemia-reperfusion(I/R)-induced edema formation, a serious drawback in lung transplantation ([ 119 ] reviewed in [ 8 ]). AT2 cells are also able to replace AT1 cells, a capacity that was, however, not dependent on TRPV4 channels [ 119 ].…”
Section: Trp Expression and Function In Alveolimentioning
confidence: 99%
“…This review will summarize TRP functions in the airways, their roles in diseases, such as chronic obstructive pulmonary disease (COPD), asthma, cystic and pulmonary fibrosis as well as lung edema. Our manuscript also serves as an update of recent reviews by us [ 5 , 6 , 7 , 8 ] and will focus on non-neuronal tissues and extensively studied TRP members, such as TRPA1, TRPC6, TRPM2, TRPM5, TRPV2 and TRPV4.…”
Section: Introductionmentioning
confidence: 99%
“…While force-sensing occurs in or on the plasma membrane, forces can reach deep in the cell interior and to the nucleus [ 80 , 81 , 82 ]. Specific mechano-transducing elements on the cell surface, including cell adhesion protein complexes, primary cilia, G protein-coupled receptors, and mechanically gated ion channels [ 29 , 83 , 84 , 85 , 86 ], have been identified in lung cells, and progress has been achieved in deciphering signaling pathways that ultimately result in physiological or pathophysiological cellular responses [ 87 , 88 ]. Part of this progress has been achieved through the development of accurate technologies for the precise application and investigation of the complex intracellular, intercellular, and cell-matrix forces affecting lung development, function, and pathophysiological processes.…”
Section: Forces On Lung Cells and Tissuementioning
confidence: 99%